Pengaruh Kepemimpinan Strategis dan Budaya Organisasi terhadap Kinerja Mahasiswa - Nita Apriyanti; Munawaroh Munawaroh (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This study aims to examine the influence of strategic leadership and organizational culture on student performance, particularly in preparing them to address global challenges and capitalize on future opportunities. The research adopts a quantitative approach, utilizing data collected through questionnaires distributed to 100 undergraduate students aged 17–27 years. The data were analyzed using validity and reliability tests, as well as descriptive analysis, with the assistance of Microsoft Excel. The findings reveal that strategic leadership significantly and positively influences student performance, especially in enhancing strategic decision-making and problem-solving skills. Moreover, a robust organizational culture substantially contributes to the development of students' character, including attributes such as collaboration, accountability, and innovation. The synergy between these two factors fosters improved student performance both academically and non-academically, equipping them to become competitive and impactful individuals in the professional world. The study recommends that higher education institutions incorporate strategic leadership elements and organizational culture values into their curricula and extracurricular activities. Future research is encouraged to broaden the sample scope and investigate additional variables, such as the role of technology in influencing student performance.